Isolation and maintenance of symbiotic fungi of ants in the tribe Attini (Hymenoptera: Formicidae) - Silva-Pinhati,Ana C.O. (2005)
The isolation and maintenance of symbiotic basidiomycete fungi living in association with ants of the tribe Attini has been hindered by the slow growth rate of these fungi and the presence of other microorganisms on the surface of the material which the ants maintain inside their nests to provide a growth substrate for their symbiont. In this paper we describe a method which increases the efficiency of isolation of these fungal symbionts by over seven fold as compared to traditional isolation procedures. Underground nests of attine ants of the genera Atta, Acromyrmex, Trachymyrmex and Mycetarotes were located, from which samples containing the fungal symbiont and ants were collected and transported to the laboratory where the ants were able to clean the fungal culture and stimulate its growth. As the symbiotic fungus grew, portions of its mycelium were collected and transferred to solid Yeast Nitrogen Base culture medium containing glucose and chloramphenicol. To facilitate the maintenance of the isolates in laboratory cultures, several nutrients were tested to formulate a complex culture medium for fast fungal growth and long-term storage. We successfully applied this methodology to the fungal symbionts of all the ant genera studied, thus producing a useful tool for the creation and maintenance of a comprehensive collection of fungi symbiotic of ants in the tribe Attini.